Discovery of URAT1 SNPs and association between serum uric acid levels and URAT1. Issue 11 (24th November 2015) - Cho, Sung Kweon; Kim, Soriul; Chung, Jae-Yong; Jee, Sun Ha
Abstract : Objectives: Human urate transporter 1 (URAT1) is a member of the organic anion transporter family (SLC22A12) that primarily regulates the renal tubular reabsorption of uric acid. This case–control study was designed to analyse whether hURAT1 might also be a candidate gene for hyperuricaemia or hypouricaemia. Setting: We recruited 68 healthy volunteers and divided them into two groups: a normal uric acid group and a hyperuricaemia group. We analysed the sequence of the URAT1 gene and found five significant single nucleotide polymorphisms (SNPs). We then selected 900 male subjects from the 262 200 enrolled in the Korean Cancer Prevention Study-II (KCPS-II) cohort for further genetic analysis. Participants: DNA samples from 36 individuals with normal uric acid (<4.5 mg/dL) and 32 individuals with hyperuricaemia (>8.5 mg/dL) were sequenced. Five significant SNPs (rs7929627, rs75786299, rs3825017, rs11602903 and rs121907892) were identified. We then chose 900 subjects from the KCPS-II cohort consisting of 450 subjects with normal uric acid (UA <4.1 mg/dL) and 450 subjects with hyperuricaemia (UA >8.7 mg/dL). The groups were matched by age, body mass index, metabolic syndrome and use of anti-hypertensive medication. Primary outcome measures: We compared the OR of the incidence of hyperuricaemia by URAT1 genotype. Results: The strongest association with hyperuricaemia was observed for rs75786299 (IVS3+11A/G) with an OR of 32.05. rs7929627 (IVS7-103A/G) and rs3825017 (N82N) showed an association with hyperuricaemia with ORs of 2.56 and 2.29, respectively. rs11602903 (788A/T) and rs121907892 (W258X) were negatively correlated with hyperuricaemia with ORs of 0.350 and 0.447, respectively. Individuals carrying the GATAG haplotype (n=32)—a relatively common variant consisting of rs7929627, rs75786299 and rs3825017—showed the highest risk for hyperuricaemia with an OR of 92.23 (p=9.55×10 −3 ). Conclusions: These results indicate that five newly described SNPs in the hURAT1 gene are significantly associated with uric acid level (4-2008-0318 and 4-2011-0277).